2012
DOI: 10.18632/aging.100527
|View full text |Cite
|
Sign up to set email alerts
|

Specific lipofuscin staining as a novel biomarker to detect replicative and stress-induced senescence. A method applicable in cryo-preserved and archival tissues

Abstract: There is shortage of extensive clinicopathologic studies of cellular senescence because the most reliable senescence biomarker, the detection of Senescence-Associated-beta-galactosidase activity (SA-β-gal), is inapplicable in archival material and requires snap-frozen tissues. We validated the histochemical Sudan-Black-B (SBB) specific stain of lipofuscin, an aggregate of oxidized proteins, lipids and metals, known to accumulate in aged tissues, as an additional reliable approach to detect senescent cells inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
230
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(256 citation statements)
references
References 37 publications
(84 reference statements)
5
230
0
5
Order By: Relevance
“…To overcome this problem, the in vivo detection of senescent cells is usually based on a combination of markers, most common of which is senescence-associated bgalactosidase staining [56], based on the fact that senescent cells are characterized by increased lysosomal content [57]. Recently, it was reported that staining of lysosomal aggregates by Sudan Black could also serve to identify senescent cells [58]. Another common feature of senescent cells is downregulation of cell cycle markers, such as KI67 or low bromodeoxyuridine (BrdU) incorporation, along with upregulation of markers for growth arrest, such as p53, p21, p16, and unphosphorylated Rb.…”
Section: Senescence: Causes and Typesmentioning
confidence: 99%
“…To overcome this problem, the in vivo detection of senescent cells is usually based on a combination of markers, most common of which is senescence-associated bgalactosidase staining [56], based on the fact that senescent cells are characterized by increased lysosomal content [57]. Recently, it was reported that staining of lysosomal aggregates by Sudan Black could also serve to identify senescent cells [58]. Another common feature of senescent cells is downregulation of cell cycle markers, such as KI67 or low bromodeoxyuridine (BrdU) incorporation, along with upregulation of markers for growth arrest, such as p53, p21, p16, and unphosphorylated Rb.…”
Section: Senescence: Causes and Typesmentioning
confidence: 99%
“…In rare cases, (stressinduced and oncogene-induced senescence), geroconversion renders cells "typically senescent," resembling senescence in vitro. 5,[106][107][108][109][110][111] A striking example is oncogene-induced senescent nevi. 112 Gerontologists are focused on these "typically" senescent cells.…”
Section: From Gerontology To Medicinementioning
confidence: 99%
“…Two methods were used for detection of ovarian lipofuscin. The first method was Sudan Black B staining following a published method (15). Briefly, non-fixed frozen ovarian sections were observed by fluorescent microscope through three channels and autofluorescent images were recorded.…”
Section: Methodsmentioning
confidence: 99%